Programação térmica fetal e duração da fase de eclosão: efeitos sobre a qualidade na eclosão, variáveis sanguíneas, preferência térmica e resposta ao desafio térmico de pintos fêmeas - Vicentini, Tamiris Iara [UNESP] (2015)
In broilers, females have a tendency to hatch earlier than males, what can leave them exposed to longer time of fasting until the access to water and feed on the farm, increasing heterogeneity and worsening the quality of the lot . This study analyzed: (1) if the tendency of females hatch earlier is associated with differences in development time or hatching, the RBC indices, the concentrations of gases and minerals in the blood, metabolism or bark characteristics, and if that changes its quality at the outbreak; (2) if the duration of the period of intra-egg pulmonary respiration, associated or not with heat stress during fetal life, interferes with the quality of the females in the outbreak, in their cardiorespiratory characteristics, hematological parameters, thermal preference and response to post-hatching thermal challenge. In Chapter 1 a theoretical approach to the subject is presented. In Chapter 2 are covered male and female birds as the duration of the hatching period, mass loss of the egg, eggshell percentage and conductance, quality of birds, biochemical and blood parameters. For this purpose, fertile eggs arrays of broilers (Cobb 500®) were incubated from day 13 under control temperature (37,5°C) or under hot (39°C). It was observed that females make the internal pipping earlier than males, and the internal pipping take less time until hatching and also the total incubation time when compared to males; They have a higher shell thickness than males. A significant difference was observed in MCV, MCH and MCHC poultry, in addition to pO2 and biochemical parameters in the blood. In chapter 3, newly hatched chicks females with short or long period between external pipping and hatching were evaluated the characteristics of the egg shells after -incubation, the yield of incubation and duration, quality, blood, heart and lung characteristics. Birds incubated under temperature at 39°C had lower shell thickness in the apical ...